FACTORS DETERMINING TAX AVOIDANCE IN ENERGY SECTOR COMPANIES IN INDONESIA - Fadhilah, Alya Nur; Kusbandiyah, Ani; Fitriati, Azmi; Pramono, Hadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to provide empirical evidence on the effect of leverage, firm size, and profitability on tax avoidance, as measured by the Effective Tax Rate (ETR). The research population consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The purposive sampling method is used in the sample selection, resulting in 102 observation data points. The statistical technique used is multiple linear regression analysis with SPSS. The results show that firm size and profitability do not have an impact on tax avoidance, while leverage has a negative effect on tax avoidance. This research contributes to the government, particularly as a basis for taking preventive measures to ensure that companies do not engage in tax avoidance.